Neonatal screening for congenital adrenal hyperplasia in Southern Brazil: a population based study with 108, 409 infants. Issue 1 (December 2017) - Kopacek, Cristiane; de Castro, Simone; Prado, Mayara; da Silva, Claudia; Beltrão, Luciana; Spritzer, Poli
Abstract Background Congenital adrenal hyperplasia (CAH) is an autosomal recessive disorder associated with inborn errors of steroid metabolism. 21-hydroxylase enzyme deficiency occurs in 90 to 95% of all cases of CAH, with accumulation of 17 hydroxyprogesterone (17-OHP). Early diagnosis of CAH based on newborn screening is possible before the development of symptoms and allows proper treatment, correct sex assignment, and reduced mortality rates. This study describes the results obtained in the first year of a public CAH screening program in the state of Rio Grande do Sul, Brazil. Methods We reviewed the screening database in search of babies with suspected CAH, that is, altered birth-weight adjusted 17-OHP values at screening. The following data were analyzed for this population: screening 17-OHP values, retest 17-OHP values, serum 17-OHP values for those with confirmed CAH on retest, maternal and newborn data, and family history of CAH. For the screening program, 17-OHP levels are determined on dried blood spots obtained in filter paper with GSP solid phase time-resolved immunofluorescence. Results Of 108, 409 newborns screened, eight were diagnosed with CAH (four males, four females). The incidence of CAH in the state was 1:13, 551. Six cases were identified as classic salt-wasting CAH and two were cases of virilizing CAH. The positive predictive value (PPV) of the initial screening (before diagnostic confirmation) was 1.6%. The overall rate of false positive results was 0.47%. The number of false positive results was higher among newborns with birth weight < 2000 g. Conclusion The present results support the need for CAH screening by the public health care system in the state, and show that the strategy adopted is adequate. PPV and false positive results were similar to those reported for other states of Brazil with similar ethnic backgrounds.